Curbing environmental degradation through energy transition in ASEAN-9: does the interactive role of political will matter? - Sulaiman, Chindo; Zubair, Azeem Oluwaseyi; Abdul Rahim, Abdul Samad (John Wiley and Sons, 2022)
This study estimates the impact of energy transition and the interactive role of political will on environmental degradation in the Association of South East Asian Nations (ASEAN) over the 1999–2020 period. Using pooled mean group and fully modified ordinary least squares estimators, the estimated results revealed that energy transition and political will have negative impact on environmental degradation in the ASEAN region. Equally, the interaction between energy transition and political will has significant negative effect on environmental degradation of the region. This implies that both energy transition and political will are significant in reducing environmental degradation through carbon dioxide emission reduction. Furthermore, strengthening political will/commitment toward energy transition process in the ASEAN countries would significantly contribute to declining environmental degradation. Thus, the study recommended a number of policy suggestions including raising the level of political commitment by governments toward energy transition to cleaner fuel is needed to achieve environmental quality in ASEAN countries.